Maternal age affects the relationship of basal FSH and anti-Mullerian hormone concentrations with post-ICSI/IVF live birth - Buratini, Jose [UNESP]; Dal Canto, Mariabeatrice; De Ponti, Elena; Brambillasca, Fausta; Brigante, Claudio; Gippone, Silvana; Renzini, Mario Mignini; La Marca, Antonio (Elsevier B.V., 2021)
Research question: Does the association of basal FSH and anti-Mullerian hormone (AMH) concentrations with post-IVF/intracytoplasmic sperm injection (ICSI) live birth change with maternal age? Design: A total of 2003 IVF/ICSI patients were stratified according to basal FSH/AMH in concordant favourable (CF; AMH >1 ng/ml and FSH <= 10 IU/l), concordant unfavourable (CU; AMH <= 1 ng/ml and FSH >10 IU/l), discordant with favourable AMH (DFA) and discordant with favourable FSH (DFF) groups, as well as according to age in pre-advanced maternal age (pre-AMA; <35), AMA-1 (>= 35, <= 37), AMA-2 (>37, <= 40) and AMA-3 (>40). IVF/ICSI outcomes were compared among CF, CU, DFA and DFF groups, and the association of basal FSH and AMH concentrations with live birth was tested by univariate and multivariate analysis in total, pre-AMA and AMA groups, separately. Results: Different outcome patterns were observed in discordant AMH/FSH groups from different age categories; favourable basal FSH concentrations were associated with higher delivery rates in pre-AMA patients, but with lower delivery rates in AMA groups. Within pre-AMA patients, DFF patients presented higher delivery rates but lower oocyte yield compared with DFA patients. In the univariate analysis, favourable AMH (P < 0.02) and oocyte yield (P < 0.002) were positively associated with live birth in all AMA groups. The multivariate analysis revealed that favourable basal FSH, but not AMH or oocyte yield, is associated with live birth in pre-AMA patients independently of other variables (P = 0.012). Conclusions: The relationship of basal FSH and AMH with IVF/ICSI success changes with maternal age; basal FSH better reflects clinical outcomes probably determined by oocyte quality in pre-AMA patients, while AMH better suits AMA patients.
Keywords: Anti-Mullerian hormone; Basal FSH; ICSI; IVF; Live birth; Maternal age